2014
DOI: 10.1017/s1041610214001951
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive parecoxib and post-operative cognitive function in elderly patients

Abstract: Background: To investigate the effect of pre-emptive parecoxib sodium, given in addition to routine analgesic treatment, on post-operative cognitive function in elderly patients. Methods: Seventy elderly patients were included, who were 65-82 years of age, 48-75 kg of weight, and ASA grade I-II. Preoperative mini mental state examination (MMSE) score was ≥21 points. Patients were randomly divided into two groups: control group (group C) and parecoxib sodium group (group P). Before induction of general anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Parecoxib was reported to decrease the incidence of postoperative cognitive dysfunction in patients after total knee arthroplasty (Zhu et al 2016 ). Similar results were presented by Tian et al ( 2014 ) and Lu et al ( 2017 ) in elderly patients that received parecoxib before general anesthesia was performed. However, celecoxib failed to improve cognitive performance in randomized controlled trial in patients with Alzheimer’s disease (ADAPT Research Group et al 2008 ), whereas according to other researchers the inhibition of cognitive decline after celecoxib administration was observed (Leoutsakos et al 2012 ).…”
Section: Discussionsupporting
confidence: 88%
“…Parecoxib was reported to decrease the incidence of postoperative cognitive dysfunction in patients after total knee arthroplasty (Zhu et al 2016 ). Similar results were presented by Tian et al ( 2014 ) and Lu et al ( 2017 ) in elderly patients that received parecoxib before general anesthesia was performed. However, celecoxib failed to improve cognitive performance in randomized controlled trial in patients with Alzheimer’s disease (ADAPT Research Group et al 2008 ), whereas according to other researchers the inhibition of cognitive decline after celecoxib administration was observed (Leoutsakos et al 2012 ).…”
Section: Discussionsupporting
confidence: 88%
“…Animal experimental study showed this cox-2 mediated neurodegeneration is related to impairments of memory parameters [20] . Clinical study confirmed that parecoxib sodium premedication could reduce the incidence of POCD, and the percent of POCD in parecoxib sodium group was 28.6% [21] , and intraoperative dexmedetomidine administration could also reduce the incidence of POCD, the percent of POCD in DEX group was 26.6% [22] . Dexmedetomidine may involve the following mechanisms to improve cognitive dysfunction: 1. inhibited inflammation [23] .…”
Section: Discussionmentioning
confidence: 74%
“…Zhu and colleagues [23] assessed the neuropsychological state of enrolled patients using a brief battery of neuropsychological test, any patient demonstrated deficit in 2 or more tests was considered as having POCD. The other three studies [2224] determined the incidence of POCD using MMSE scale, POCD was defined if the difference between post- and preoperative MMSE score was equal or larger than the standard deviation of preoperative MMSE scores…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [22,24] reported clinical characteristics and postoperative situation, such as consumption of analgesic and nausea. In the study conducted by Mu et al, the incidence of nausea and vomiting, NRS pain score at rest and cumulative morphine consumption were lower in parecoxib group than control group.…”
Section: Resultsmentioning
confidence: 99%